Establishment of Taxable Entrepreneurs (Pkp) Forretail Traders Based On Per-03/Pj/2022 - Renny Anggraeni; Mochamad Saleh (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
Tax is one of the Government's sources of income to carry out development and for that the State imposes it on its people. One type of tax is Value Added Tax (PPN) where VAT is a tax imposed due to the delivery of Taxable Goods (BKP) and/or Taxable Services (JKP). One of the VAT subjects is a Retail Trader (PE), which is defined as carrying out a direct delivery transaction to the final buyer (end-user). Based on Tax Regulation Number PER-03/PJ/2022, the requirements to become a PE plus the submitted BKP/JKP are not used for production activities first. This study aims to find out whether the determination of the classification of PKP PE based on PER-03/PJ/2022 is in accordance with the VAT Law and the requirements for classifying PE have fulfilled the principle of fairness. This study uses a juridical-normative method with a statutory and conceptual approach. This research gives the result that the Directorate General of Taxes issues regulations based on the authority of a delegation from the Minister of Finance and its main task is to formulate and implement policies in the field of taxation. Related to the additional conditions for determining PE, it deviates from the VAT Law because it is not regulated in the VAT Law, while the position of PER-03/PJ/2022 based on State Administrative Law is a policy regulation (beleidsregel). Based on Article 8 of Law no. 12 of 2011, PER-03/PJ/2022 does not include legal rules that are recognized by the legal system in Indonesia but their existence is recognized because there is authority obtained (delegation) and when viewed from the principle of justice, the addition of these conditions has saved a sense of justice because it results in PE who should be included in the category are not classified as PKP PE so that they cannot enjoy the facilities as PKP PE based on the VAT Law.